Clinical Profile of Children with Thalassemia Admitted for Blood Transfusion at a Tertiary Health Care Center - Tiwari, Damodar; Gupta, Sweta Kumari; Thapa, Narayan Bahadur; Devkota, Kiran (Journal of College of Medical Sciences-Nepal, 2023)
Introduction Thalassemia is a prevalent hereditary hematological disorder that is characterized by a reduction or absence of globin chain synthesis. The objective of this study is to determine the clinical profile of children with thalassemia who undergo repeated packed cell transfusions. Methods A prospective cross-sectional observational study was conducted from January 1, 2023, to May 31, 2023, in the Pediatric ward at Bharatpur Hospital. Ethical clearance was obtained from the Institutional Review Committee of Bharatpur Hospital (Ref: 078/79-018). A total of 53 cases of Thalassemia, who were receiving regular blood transfusions, were included in this study. Results The prevalence of thalassemia was 3.68% (with 95% CI 2.7% to 4.65%). The average age at diagnosis was 15.58 months, with a range of 2 to 97 months. The majority of cases, 32 (60.37%), were diagnosed before the age of one year, with a male-to-female ratio of 1.2:1. Thalassemia was more prevalent in the Tharu community (58.5%) compared to other communities. Conclusions Thalassemia is a hematological disorder that predominantly affects the Tharu community. Common clinical manifestations of transfusion-dependent thalassemia in children include pallor, hepatomegaly, splenomegaly, and facial deformities. Therefore, it is imperative to monitor serum ferritin levels to detect iron overload early and initiate chelation therapy promptly to prevent complications. Such measures can significantly improve the quality of life of affected individuals and reduce the burden of this genetic disorder on affected communities.